The Effectiveness of Mix Impact Aerobic Gymnastics Exercises With SKJ 2000 On Improvement of Physical Freshness - Anik Maryani; Fahmy Fachrezzy; Ramdan Pelana (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
This study aims to determine the effectiveness of the effect of aerobic mix impact and SKJ 2000 version (core exercise) to improve physical fitness in female students. The research was conducted at SMEA YASMA Sudirman Cijantung for 8 weeks with 24 meetings. The method used is an experimental method with a pre and post-test design. The sampling technique was random sampling from a total of 40 grade 1 students and 30 samples were taken. The data collection technique used was a physical fitness test using the Indonesian Physical Fitness Test (TKJI). Hypothesis testing uses the t-test at the significant level (α) 0.05. The results showed that the difference between the mean value of the initial test (x) and the final test (y) in the mixed impact aerobic exercise group was obtained = -6.47; the value of the standard deviation of the difference = 1,2; the standard error value of the mean difference = 0.32; and the value becomes = -20,2. The initial test (x) and the final test (y) in the 2000 version of the Physical Fitness exercise obtained the difference in the mean value is = -5; the value of the standard deviation of the difference = 1.1; the standard error value of the mean difference = 0.29; and the value becomes = -17.24. The final test of the mixed impact aerobic exercise group (x) and the final test of the aerobic exercise group (y) version 2000, obtained the mean value of the variable x = 19.33; variable value y = 17; the standard deviation value x = 1.48; standard deviation of the variable y = 2.31; standard error variable x = 0.4; standard error for the variable y = 0.62; standard error for the mean difference between x and variable = 0.74; Hypothesis test results obtained t observation = 3.15, at 28 degrees of freedom and a significant level (α) 0.05, the value of t table = 2.048 is obtained. The conclusion of the study is that the effect of mix impact aerobic exercise is more effective in improving physical fitness compared to those using the 2000 version of the fitness gymnastics version of aerobic exercise.